KEDUDUKAN ANAK HASIL ZINA DITINJAU DARI HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Lukman Hakim (Universitas Muhammadiyah Sumatera Utara, 2016)
The child of adultery has been controversial in law when it comes to talk about the rights that it should have. The controversy related to the line of descent, disinherited and other rights associated with the law. Islamic law considers the child of adultery naturally has the line of descent with his mother as well as disinherited. On the other side of the existing regulations in Indonesia, particularly Article 867 to Article 869 of the Civil Code, that child of adultery cannot be an heir of her mother and her biological father, they are only entitled to subsistence necessary.